Assuring M2M secure transactions via blockchain and cmart contracts - Leite, Nuno (2021)
The need to ensure the confidentiality and integrity of data generated in industrial systems and applications has been increasingly highlighted over the years, due to the clear as well as urgent requirements of not disclosing sensible proprietary information, and ensuring that data is kept immutable since it is generated. Based on these background requirements, this paper discusses a system that promotes data privacy and immutability in industrial weighing systems. In this sense, the proposed solution includes a protocol definition for a secure IoT (Internet of Things) communication and an architecture for a blockchain-based platform that: i) automates the process of complying with standardized weighing guidelines; and ii) increases data traceability, promoting both its confidentiality and immutability. Additionally, to demonstrate the proposed system's compliance with the established goals, a proof of concept was assembled, and functional tests conducted. The main conclusions withdrawn from the results obtained show that: i) the process of registering and verifying weighing guidelines is properly automated by means of Machine-to-Machine secure transactions; ii) the solution is able to ensure that the data registered is authentic and iii) that it has been transmitted without any eavesdropping, can not be erased and is kept private.